Aspects of the geology and mineragraphic studies of stratabound lead-Zinc Orebodies at song toh mine, Kanchanaburi - Pichya Permthong (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 1982